Use of ionic liquid for X-ray micro-CT specimen preparation of imbibed seeds. (13th November 2018) - Yamauchi, Daisuke; Fukuda, Aki; Nakai, Tomonori; Karahara, Ichirou; Takeuchi, Miyuki; Tamaoki, Daisuke; Tsuda, Tetsuya; Tsunashima, Katsuhiko; Kuwabata, Susumu; Hoshino, Masato; Uesugi, Kentaro; Takeuchi, Akihisa; et al.
Abstract : We developed a novel specimen preparation method for X-ray micro-CT observation of wet biological samples using ionic liquids. Treatment with high concentrations of ionic liquids after osmium tetroxide fixation helped not only to prevent shrinkage but also to maintain the cellular architecture of imbibed Arabidopsis seeds. Abstract: X-ray micro-CT is one of the most useful techniques to examine 3D cellular architecture inside dry seeds. However, the examination of imbibed seeds is difficult because immersion in water causes a decline in the image quality. Here, we examined the use of ionic liquids for specimen preparation of chemically fixed imbibed seeds of Arabidopsis. We found that treatment with high concentrations of ionic liquids after osmium tetroxide fixation helped not only to prevent the structural damage caused by seed shrinkage, but also to preserve the image quality. Under these conditions, the cellular architecture of seeds was also well maintained.